Challenges in Implementing the Qanun Jinayat in Aceh: A Legal Certainty Analysis of Sharia Law Enforcement - Muhammad Syarif; Wahyuddin Wahyuddin; Fauzan Fauzan (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study analyzes the effectiveness of the implementation of Aceh Qanun No. 6 of 2014 on Islamic Criminal Law (Jinayat) from the perspective of legal certainty within Aceh’s plural legal system. The study is motivated by empirical problems indicating that the enforcement of jinayat law has not been consistently implemented, as reflected in disparities among legal actors, the coexistence of customary law and formal jinayat procedures, and the persistence of vigilante justice practices in society. This research employs a normative legal method with statutory, conceptual, and case approaches. The analysis is framed using Soerjono Soekanto’s theory of legal effectiveness and Lawrence M. Friedman’s legal system theory. The findings indicate that the ineffectiveness of jinayat law enforcement is not solely caused by deficiencies in legal substance, but also by structural weaknesses in legal institutions and legal culture that have not yet functioned in a harmonized manner within Aceh’s plural legal order. The novelty of this study lies in its integrative approach, combining legal effectiveness theory and legal pluralism to explain the causal relationship between institutional fragmentation, societal legal culture, and the low level of legal certainty in the enforcement of Islamic law in Aceh. This study contributes theoretically by strengthening the analytical framework of legal effectiveness in the context of regional Islamic law, and practically by offering policy recommendations for institutional harmonization and improved integration between customary law and formal legal systems. The study concludes that strengthening coordination among legal institutions, enhancing legal awareness, and harmonizing legal pluralism are essential to improving legal certainty in the enforcement of Islamic criminal law in Aceh.